Massagem com aromaterapia e sua eficiência para o usuário em internação psiquiátrica - Domingos, Thiago da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Psychiatric nursing and mental health care have followed the numerous changes that have taken place in medicine and in the social, historical and cultural realms. Hence, care provision to patients with mental disorders has been outlined in light of the Psychiatric Reform and Psychosocial Rehabilitation based on precepts such as humanization, resocialization and reintegration of such users into society, thus causing abrupt changes in the micro policies of work, in health care team members, in patients’ relatives and in care provision devices in the mental health care network. With the purpose to pluralize care practices in the Unified Public Health System (SUS), complementary practices have been available in Brazil since 1970, although in a non-systematized fashion. In 2006, the Health Department (HD) published the National Policies for Integrative and Complementary Health Care Practices (Política Nacional de Práticas Integrativas e Complementares em Saúde [PNPIC]), thus ensuring to professionals the application of such techniques. Among such practices, aromatherapy is mentioned, and its use has presently increased in Nursing as one of the main professional classes representing that therapy type. It consists in the use of essential oils by means of inhalation, dermal application and smelling, with the purpose of prevention and treatment. Therefore, this study aims at analyzing the efficacy of massage with aromatherapy on the anxiety of patients hospitalized in a psychiatric hospitalization unit, using, as parameters, a nationally and internationally validated anxiety scale (STAI), the measurement of heart and respiratory rates and users’ experience in relation to that practice. It is a quanti-qualitative study with a non-controlled clinical-trial design applied in the psychiatric hospitalization unit of the Marilia School of Medicine University Hospital (FAMEMA). The population in the study consisted of fifty subjects ...

A enfermagem psiquiátrica e o cuidado em saúde mental têm acompanhado as inúmeras modificações que têm acontecido no âmbito da medicina e nas esferas social, histórica e cultural. Com isso, o cuidado ao portador de transtornos mentais tem se delineado à luz da Reforma Psiquiátrica e da Reabilitação Psicossocial, militando-se por preceitos como a humanização, a ressocialização e a reintegração desses usuários à sociedade. Assim, ocasionando mudanças bruscas na micropolítica do trabalho, nos profissionais da equipe de saúde, nos familiares e nos dispositivos de cuidado na rede em saúde mental. No sentido de pluralizar as práticas de cuidado no Sistema Único de Saúde (SUS), conta-se desde 1970 com as práticas complementares no Brasil, no entanto, de forma não sistematizada. Em 2006, o Ministério da Saúde (MS) publicou a Política Nacional de Práticas Integrativas e Complementares em Saúde (PNPIC), assegurando para os profissionais a aplicação dessas técnicas Dentre essas práticas cita-se aromaterapia, cuja utilização tem crescido atualmente e a enfermagem como sendo uma das principais classes profissionais representante desta terapia. Consiste na utilização de óleos essenciais por meio da inalação, aplicação dérmica e olfação, com objetivo de prevenção e tratamento. Dessa forma, este estudo tem como objetivo analisar a eficácia da massagem com aromaterapia sobre a ansiedade de pacientes internados em uma unidade de internação psiquiátrica, tendo como parâmetros uma escala de ansiedade validada nacional e internacionalmente (IDATE), a mensuração das frequências cardíaca e respiratória e a experiência do usuário em relação a esta prática. Trata-se de um estudo quanti-qualitativo, com delineamento de ensaio clínico não controlado, aplicado na unidade de internação psiquiátrica do Hospital das Clínicas da Faculdade de Medicina de Marília (FAMEMA). A população de estudo foi ...
Keywords: Ansiedade; Aromaterapia; Essencias e oleos essenciais - Uso terapeutico; Enfermagem psiquiatrica; Massagem; Aromatherapy